Measurement of the Cytoplasmic pH in Nitella translucens: Comparison of Values Obtained by Microelectrode and Weak Acid Methods - Spanswick, Roger M. (1977)
A comparison has been made between the use of two types of pH microelectrode and the weak acid method for determining the cytoplasmic pH of Nitella translucens at an external pH of 6. There was good agreement between the value obtained with glass pH microelectrodes (7.54 ± 0.15 se) and that obtained using the weak acid 5,5-dimethyloxazolidine-2,4-dione (7.42 ± 0.07 se). Plastic-insulated antimony microelectrodes gave a significantly lower value (6.74 ± 0.15 se) possibly due to disruption of the insulation by the cell wall. The addition of 1 mM NaN(3) rapidly reduced the pH recorded by the glass pH microelectrodes to about 5.3. A smaller change was observed using the weak acid method. The relevance of this observation to recent work on indoleacetic acid transport is discussed.